Antimicrobial resistance of Clostridioides difficile in veterinary medicine around the world: A scoping review of minimum inhibitory concentrations - Mauricio Andino-Molina; Ines Dost; Mostafa Abdel-Glil; Mathias W. Pletz; Heinrich Neubauer; Christian Seyboldt (One Health)
Objective: To provide a comprehensive characterization of Clostridioides difficile antimicrobial resistance (AMR) data in veterinary medicine based on the minimum inhibitory concentrations (MICs) of all antimicrobial agents tested in relation to the techniques used. Methods: A systematic scoping review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews (PRISMA-ScR) and its associated checklist. The objective was to provide a synthesis of the evidence in a summarized and analyzed format.To this end, three scientific databases were consulted: Scopus, PubMed, and Web of Science, up until December 2021. Subsequently, all identified literature was subjected to screening and classification in accordance with the established study criteria, with the objective of subsequent evaluation. Study selection and data extraction: A comprehensive analysis was conducted on studies regarding Clostridioides difficile antimicrobial resistance (AMR) in veterinary medicine across various animal species and related sources. The analysis included studies that presented data on antimicrobial susceptibility testing using the E-test, agar dilution, or broth microdilution techniques. The extracted data included minimum inhibitory concentration (MIC) values and a comprehensive characterization analysis. Results: A total of 1582 studies were identified in scientific databases, of which only 80 were subjected to analysis. The research on Clostridioides difficile antimicrobial resistance (AMR) in veterinary medicine is most prolific in Europe and North America. The majority of isolates originate from production animals (55%) and pets (15%), with pigs, horses, and cattle being the most commonly studied species. The tested agents' minimum inhibitory concentrations (MICs) and resulting putative antimicrobial resistance profiles exhibited considerable diversity across animal species and sources of isolation. Additionally, AMR characterization has been conducted at the gene and genomic level in animal strains. The E-test was the most frequently utilized method for antimicrobial susceptibility testing (AST). Furthermore, the breakpoints for interpreting the MICs were found to be highly heterogeneous and frequently observed regardless of the geographical origin of the publication. Conclusions: Antimicrobial susceptibility testing techniques and results were found to be diverse and heterogeneous. There is no evidence of an exclusive antimicrobial resistance pattern in any animal species. Despite the phenotypic and genomic data collected over the years, further interdisciplinary studies are necessary. Our findings underscore the necessity for international collaboration to establish uniform standards for C. difficile antimicrobial susceptibility testing (AST) methods and reporting. Such collaboration would facilitate a “One Health” approach to surveillance and control, which is of paramount importance.